Does a Clarke-Groves type tax prevent free riding when implementing Eurobonds? - Carlos Contreras; Julio Angulo (Applied Economic Analysis, 2021)
Purpose – The purpose of this paper is to propose a Clarke-Groves Tax (CGT) type as a remedy to the criticism that the implementation of Eurobonds has raised regarding the risk of undermining fiscal discipline. In this model, a government minimizes its sovereign debt-to-GDP ratio in a given period and decides whether to join a common sovereign debt club. In doing so, it exposes itself to a positive or negative tax burden while benefiting from the liquidity premium involved in creating a secure asset. The authors found that the introduction of this tax may prevent free riding behaviours if Eurobonds were to be implemented. To illustrate this, the authors provide some numerical simulations for the Eurozone. Design/methodology/approach – In the model presented, a government which optimizes a social utility function decides whether to join the common debt club. Findings – The adoption of the proposed tax could prevent free-riding behaviours and, therefore, encourages participation by those countries with lower debt levels that would have not otherwise taken part in this common debt mechanism. Under certain circumstances, we can expect the utility of all members of this club to improve. The bias in the distribution of gains might be mitigated by regulating the tax rule determining the magnitude of payment/reward. The proportion of the liquidity premium, arising from the implementation of a sovereign safe asset, has a decisive impact on the degree of the governments’ utility enhancement. Research limitations/implications – The adoption of a CGT would require Eurobonds club members to reach an agreement on “the” theoretical model for determining the sovereign debt yield. One of the limitations of this model is considering the debt-to-GDP ratio as the sole determinant of public debt yields. Moreover, the authors assumed the relationship between the debt-to-GDP ratio and funding costs to be identical for all countries. Any progress in the implementation of the proposed transfer scheme would require a more realistic and in-depth analysis. Practical implications – A new fiscal rule based on compensating countries with lower public debt levels could be a way to mitigate free-riding problems if a Eurobond mechanism is to be established. Originality/value – This fiscal rule has not been proposed or analysed before in a context such as that considered by this paper.